The Role Of Budget Information Systems In Enhancing Accountability and Budget Utilization In The Regional Apparatus Organizations Of Southwest Papua Province - Deasy Ludia Arisandi Kambuaya; Vebby Anwar; Rosdinaman Budi; Amiruddin (International Journal of Management and Business Economics, 2026)
This study examines the effect of budget information systems on budget utilization through accountability in the Regional Apparatus Organizations (SKPD) of Southwest Papua Province. The research employed a quantitative approach with an explanatory design. Data were collected through questionnaires distributed to 50 respondents involved in budget management across the selected regional apparatus organizations and were analyzed using descriptive statistics with SPSS 26 and Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that budget information systems have a positive and significant effect on accountability, budget information systems have a positive and significant effect on budget utilization, and accountability has a positive and significant effect on budget utilization. Furthermore, accountability mediates the relationship between budget information systems and budget utilization. These results indicate that effective budget information systems, supported by strong accountability mechanisms, contribute to improving the utilization of public budgets within regional government organizations. This study is limited by its relatively small sample size and its reliance on perception-based data collected during a single observation period. The originality of this study lies in examining the mediating role of accountability in the relationship between budget information systems and budget utilization within regional government organizations in Southwest Papua Province.